2001
DOI: 10.1074/jbc.m101637200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fertilin α (ADAM1)-mediated Sperm-Egg Cell Adhesion during Fertilization and Identification of an Adhesion-mediating Sequence in the Disintegrin-like Domain

Abstract: Fertilin ␣ (also known as ADAM1) is a member of the ADAM (A disintegrin and A metalloprotease domain) family of proteins. In this study, we examine the mechanism of mouse fertilin ␣'s in adhesion of sperm to the egg plasma membrane during fertilization. We find that recombinant forms of fertilin ␣ corresponding to either the disintegrin-like domain or the cysteine-rich domain and the EGF-like repeat can perturb sperm-egg binding, suggesting that both of these domains can participate in fertilin ␣-mediated adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…In constrast, CD9 was reported to play a role in sperm-oocyte binding. Zona pellucida-free oocytes treated with anti-CD9 antibodies showed reduced levels of binding to the ligands; fertilin a, fertilin b and cyritestin on sperm when the antibodies were immobilized on small beads , Takahashi et al 2001, Wong et al 2001, Zhu & Evans 2002. Although the functional difference between the lack of CD9 and treatment with anti-CD9 antibodies is not clear, the antibodies may disturb the strength of adhesions mediated by a molecule such as a6 integrin involved in the multi-protein complex together with CD9.…”
Section: Introductionmentioning
confidence: 91%
“…In constrast, CD9 was reported to play a role in sperm-oocyte binding. Zona pellucida-free oocytes treated with anti-CD9 antibodies showed reduced levels of binding to the ligands; fertilin a, fertilin b and cyritestin on sperm when the antibodies were immobilized on small beads , Takahashi et al 2001, Wong et al 2001, Zhu & Evans 2002. Although the functional difference between the lack of CD9 and treatment with anti-CD9 antibodies is not clear, the antibodies may disturb the strength of adhesions mediated by a molecule such as a6 integrin involved in the multi-protein complex together with CD9.…”
Section: Introductionmentioning
confidence: 91%
“…Further evidence has indicated that sperm were able to adhere to the plasma membrane of zona pellucida (ZP)-free oocytes from CD9 knockout mice; however, very few sperm could fuse with the oocyte membrane (Le Naour et al 2000, Miyado et al 2000. Reduced sperm binding was also found in ZP-free mouse oocytes treated with anti-CD9 monoclonal antibodies , Takhashi et al 2001, Wong et al 2001, Zhu & Evans 2002. Sperm -oocyte fusion was also decreased when the oocytes treated with anti-CD9 antibody were inseminated (Miller et al 2000).…”
Section: Introductionmentioning
confidence: 92%
“…2B demonstrate that the toxin encoding ESTs are dominated by SVMPs (58%) and bradykinin-potentiating peptides (18%) relative to PLA 2 s and CTLs (both 9%) with lower (1-2%) relative expression levels of serine proteinases, growth factors and L-amino oxidases. Examination of the GOannotated proteolysis and peptidolysis category also identified two clusters of novel aspartic proteases representing 2% of a Position analogous to IB-I (α 2 β 1 ) ECD-like motif (Kamiguti et al, 1997;Zhu et al, 2000;Wong et al, 2001). b Conserved IB-Ib (α 9 β 1 ) motif in ADAMS (Eto et al, 2000).…”
Section: Toxin Cataloguing and Identificationmentioning
confidence: 97%